HAK NASAB, PEMBERIAN NAMA YANG BAIK, DAN ASI EKSKLUSIF - Rasyid Siddiq; Faisar Ananda (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study discusses the rights of lineage (nasab), the importance of giving good names, and exclusive breastfeeding from the perspectives of Islamic law and positive law in Indonesia. These three aspects are fundamental rights of children that must be fulfilled by parents from birth. This study aims to examine the concept of nasab in Islamic law, the obligation of parents to provide good names, and the importance of exclusive breastfeeding for child development. The method used is normative legal research with a juridical approach through literature studies of primary and secondary legal sources, including the Qur'an, Hadith, Compilation of Islamic Law, and relevant legislation. The results show that Islamic law and Indonesian law emphasize the fulfillment of children's basic rights, including identity, dignity, and physical well-being, which are reflected in nasab recognition, proper naming, and breastfeeding. These rights are essential to ensure optimal growth and development of children.